Feed plants, ethnoveterinary medicine, and biocultural values: insights on the Luchuan pig from Hakka communities in China - Yongqing Liufu; Jilong Zhou; Qiongyao Fu; Min Shao; Yaozhang Xie; Binsheng Luo (BMC, 2023)
Abstract Background The Luchuan pig is an indigenous breed from Luchuan County, China, with cultural and genetic significance. However, traditional knowledge and conservation status have not been systematically documented. Methods Using ethnobiological methods, we surveyed 72 Luchuan pig farmers in 7 townships during 2021-2023. Semi-structured interviews and participant observation were conducted to document traditional knowledge and management practices. Results The locals reported 51 plant species used as pig feed, with 30 wild species. Growth-stage-specific feeding and seasonal adjustment practices were documented. We recorded 62 ethnoveterinary plant uses, mainly for treating pigs' heat stress and skin conditions. Luchuan pigs play central roles in local Hakka customs, rituals, and cuisine. Additonally, the new ecological farming models minimize the environmental impacts to the local community. However, there are still some challenges remained for conserving and promoting Luchuan pigs. Conclusions The Luchuan Hakka people possess rich traditional knowledge and management experience in raising Luchuan pigs. Our study provides extensive documentation of traditional knowledge and recommends integrating cultural and genetic aspects for sustaining this biocultural heritage. Findings can inform initiatives supporting local breed conservation globally.